Acid-Free Nitration of Benzene and Toluene in Zeolite NaZSM-5. (28th February 2013) - Kirkby, Scott J.
Abstract : The syntheses of nitrobenzene and p-nitrotoluene directly from benzene, toluene, and NO2 within the pore network of the initially acid-free zeolite NaZSM-5 are reported for the first time. The active species NO 2 δ +, formed by the interaction of NO2 with the Na + cations present on the internal surface, results in the acid-free electrophilic substitution of the aromatic ring. There are two distinct reservoirs for the reagents: one associated with close proximity to the cation sites and the other associated with the siliceous areas of the pore network. Up to 34% of the hydrocarbon and 70% of the available NO2 are reacted at 50°C. Only the cation associated sites are reactive at low temperature, and there appears to be little mobility between the sites under the reaction conditions. There is no evidence of a second nitration occurring. This represents a novel route to the single nitration of benzene and toluene and for toluene, the generation of the para isomer exclusively. The pore network of the NaZSM-5 restricts the available reaction volume and transition state geometry allowing only the para-substituted product.